2023
DOI: 10.1088/1361-6501/acc2db
|View full text |Cite
|
Sign up to set email alerts
|

A multi-stream multi-scale lightweight SwinMLP network with an adaptive channel-spatial soft threshold for online fault diagnosis of power transformers

Abstract: The fault diagnosis of power equipment is extremely crucial to the stability of the power grid system. However, complex operating environments, high costs and limitations of single-modal signals are the biggest bottlenecks. To this end, a Multi-Stream Multi-Scale Lightweight SwinMLP Network (MLSNet) with adaptive channel-spatial soft threshold is proposed in this paper. First, a Res2net-based feature-enhanced method is used to learn the correlated features of vibration and voltage multi-modal signals. Second, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The swin transformer block is shown in figure 3(a) using the shifted windows as a foundation [21]. It consists of a two-layer MLP, a layer normalization (LN) layer, a window-based MSA module, and a residual connection that makes up each swin transformer block.…”
Section: St-sparse Swin Transformermentioning
confidence: 99%
See 2 more Smart Citations
“…The swin transformer block is shown in figure 3(a) using the shifted windows as a foundation [21]. It consists of a two-layer MLP, a layer normalization (LN) layer, a window-based MSA module, and a residual connection that makes up each swin transformer block.…”
Section: St-sparse Swin Transformermentioning
confidence: 99%
“…The combination of graphic modeling techniques and deep learning (DL) techniques have proven to be successful and beneficial in fault identification. Various DL-based techniques, such as CNNs [17][18][19], Res2Net [20], RNNs, transformer [16], and swin transformer [21], have been extensively employed for this purpose. For instance, the deep residual shrinkage network [22] is an innovative DL architecture that utilizes a soft threshold approach, serving as a CNN variant specifically designed to handle noise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [22] reported a method combining 1D CNN and ViT to recognize engine faults, and the experimental results showed its effectiveness. Liu and He [23] presented a multi-stream multi-scale lightweight SwinMLP network for online fault diagnosis of power transformers. However, the ViT also exists the shortcomings, for example the complex model structures and the too large number of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Power systems are critical infrastructures in modern society. As the core device of a power system, regular operation of transformers is crucial for stable operation [1]. However, the occurrence of abnormal faults in transformers is inevitable, timely repairs to prevent economic losses.…”
Section: Introductionmentioning
confidence: 99%